Autobiographical amnesia and accelerated forgetting in transient epileptic amnesia. Issue 10 (16th September 2005) - Manes, F; Graham, K S; Zeman, A; de Luján Calcagno, M; Hodges, J R
Abstract : Background: Recurrent brief isolated episodes of amnesia associated with epileptiform discharges on EEG recordings have been interpreted as a distinct entity termed transient epileptic amnesia (TEA). Patients with TEA often complain of autobiographical amnesia for recent and remote events, but show normal anterograde memory. Objective: To investigate ( a ) accelerated long term forgetting and ( b ) autobiographical memory in a group of patients with TEA. Methods: Seven patients with TEA and seven age matched controls were evaluated on a range of anterograde memory tasks in two sessions separated by 6 weeks and by the Galton-Crovitz test of cued autobiographical memory. Results: Patients with TEA showed abnormal long term forgetting of verbal material, with virtually no recall after 6 weeks. In addition, there was impaired recall of autobiographical memories from the time periods 1985–89 and 1990–94 but not from 1995–1999. Conclusions: TEA is associated with accelerated loss of new information and impaired remote autobiographical memory. There are a number of possible explanations including ongoing subclinical ictal activity, medial temporal lobe damage as a result of seizure, or subtle ischaemic pathology. Future analyses should seek to clarify the relationship between aetiology, seizure frequency, and degree of memory impairment.